What's yours is mine : open access and the rise of infrastructure socialism - Thierer, Adam D. (Cato Institute, 2003)
N What's Yours Is Mine: Open Access and the Rise of Infrastructure Socialism, authors Adam Thierer and Clyde Wayne Crews Jr. examine the hazards of mandatory "open access"--A new trend in which hyper-regulatory bureaucrats and central planners are increasingly commanding technology companies and industry sectors to share networks, facilities, or specific technologies with rivals